Antioxidant activity of winter melon (Benincasa Hispida) seeds using conventional soxhlet extraction technique - B., Mandana; Abdul Rahman, Russly; S. T., Farah; Mohd Adzahan, Noranizan; Sarker, Md. Zaidul Islam; Ganjloo, Ali (University Putra Malaysia, 2012)
In this study, the effect of different solvent including ethanol, n-hexane and ethyl acetate on antioxidant activity and total phenolic content (TPC) of winter melon (Benincasa hispida) seeds extract was investigated using conventional Soxhlet extraction (CSE). DPPH and ABTS scavenging activity and TPC results indicated that the seed extracts obtained using ethanol possessed the highest antioxidant activity and followed by ethyl acetate and n-hexane. By considering obtained results, it was clear that there was a high positive correlation between TPC and antioxidant activity. Linoleic acid forms a significant percentage of unsaturated fatty acids of the seed extract (60.6%). It is well known that essential fatty acids including linoleic acid and linolenic acid which are detected in extracts play important roles in preventing many disease and abnormal differentiation problems. B. hispida seeds are potential source of natural antioxidant compounds to replace synthetic antioxidants.